Extracellular vesicles from activated platelets: a semiquantitative cryo-electron microscopy and immuno-gold labeling study. (3rd April 2017) - Brisson, Alain R.; Tan, Sisareuth; Linares, Romain; Gounou, Céline; Arraud, Nicolas
ABSTRACT: Cells release membrane vesicles in their surrounding medium either constitutively or in response to activating signals. Two main types of extracellular vesicles (EVs) are commonly distinguished based on their mechanism of formation, membrane composition and size. According to the current model, EVs shed from the plasma membrane, often called microvesicles, expose phosphatidylserine (PS) and range in size from 100 nm to 1 µm, while EVs originating from endosomal multi-vesicular bodies, called exosomes, contain tetraspanin proteins, including CD63, and range in size from 50 to 100 nm. Heijnen et al. [1] have shown that activated platelets release EVs corresponding to these two types of vesicles, using negative staining electron microscopy (EM) and immuno-gold labeling. Here, we apply cryo-EM and immuno-gold labeling to provide a quantitative analysis of EVs released by platelets activated by thrombin, TRAP and CRP-XL, as well as EVs from serum. We show that EVs activated by these three agonists present a similar size distribution, the majority of them forming a broad peak extending from 50 nm to 1 µm, about 50% of them ranging from 50 to 400 nm. We show also that 60% of the EVs from TRAP or CRP-XL activation expose CD41, a majority of them exposing also PS. To explain the presence of large EVs CD41-negative or PS-negative, several alternative mechanisms of EV formation are proposed. We find also that the majority of EVs in activated platelet samples expose CD63, and distinguish two populations of CD63-positive EVs, namely large EVs with low labeling density and small EVs with high labeling density.